The American no : stories - Everett, Rupert (Atria Books, 2025)
"In his first, glorious collection of stories, Rupert Everett takes us on exhilarating journeys with a cast of extraordinary characters. From Oscar Wilde's last night in Paris to the ferociously unforgiving world of a Los Angeles talent agency and beyond, these stories are evocative, moving, and tender. Brilliantly witty, elegiac, and drawing from the wealth of film and TV ideas Everett has worked on over the course of his illustrious career, The American No will delight and surprise his many fans" --